Learning and Community Approaches for Promoting Well-Being - Kee, Youngwha; Kim, Yunji; Phillips, Rhonda (SpringerBriefs in Well-Being and Quality of Life Research, 2015)
This Brief provides perspectives on bringing together elements of learning and community approaches for promoting overall wellbeing. Drawing on experiences of authors from across Asia, Europe, and North America, cases are presented to illustrate both policy and application of adult learning, child wellbeing, community integration and learning, as well as intergenerational cooperation. Starting with foundational concepts of community wellbeing and community learning, the briefs provides an exploration of constructs and ideas for exploring application. The remaining chapters detail cases of community wellbeing, providing insights on approaches, as well as self-generated processes. Policy approaches, whether driven by local governance or from within individual organizations or sectors of communities, are discussed in addition to outcomes generated by the approaches.